Peer-led team learning. the workshop project - Strozak, Victor S. 1940-; Gosser, David K.; Cracolice, Mark S. (Prentice Hall series in educational innovation, 2006)
Workbook developed from the Workshop Chemistry Project which explored, developed and applied the concept of peer-led team learning in problem-solving workshops in introductory chemistry courses.